Effect of polyethylene glycol on pore structure and separation efficiency of silica-based monolithic capillary columns - Hara, Takeshi; Desmet, Gert; Baron, Gino V.; Minakuchi, Hiroyoshi; Eeltink, Sebastiaan (Journal of Chromatography A, 2016)
•We investigated the effect of PEGs on the structure of monolithic silica capillary columns.•Columns with smaller domain size than previous 2nd generation monoliths were developed.•Improved kinetic performance in the region of N≤40,000 plates is obtained.•Performance improvement is due to smaller domain size and better homogeneity. Monolithic silica materials (first unclad monolith rods, then monolithic capillary columns) were prepared using various amounts of polyethylene glycols (PEGs) with different molecular weight (MW). The monolith rods were used to examine the mesoporosity by argon physisorption technique, and the macroporosity by mercury intrusion porosimetry. Subsequently, silica-based monolithic capillary columns with an inner diameter of 100μm were produced using the same preparation conditions as used for the rods. The results obtained with the monolith rods showed the following important findings: (1) it is feasible to fabricate monolithic silica rods possessing macropore size of 0.5–1.4μm by tuning the amount of PEGs (independently of the MW), whereas the macropore volume and the mesoporosity remain similar. (2) the smallest macropore size (0.5μm) rod prepared with PEG having a MW=20,000g/mol provided a narrower macropore size distribution than with PEG with MW=10,000g/mol. The monolithic capillary columns produced with the different PEG type showed similar retention factors for hexylbenzene (k=2.3–2.4) and similar t0-based column permeability (Kv0=2.3–2.4×10−14m2) in 20:80% (v/v) water:methanol, as expected from the results obtained with the monolith rods. The column prepared with PEG of MW=20,000g/mol gave a plate height of H=4.0μm for hexylbenzene at an optimal linear velocity of u0=2.6mm/s in 20:80% (v/v) water containing 0.1% formic acid:acetonitrile. To the best of our knowledge, this is the lowest plate height ever recorded for a monolithic column. Comparing the kinetic performance at 30MPa shows that the best monolithic silica column obtained in the present study performs better than the second-generation monolithic silica columns developed up till now in the practically most relevant range of plate numbers (N≤40,000). In this range, the performance is now similar to that of 2.7μm core-shell particle columns.